Pulsatile and steady components of blood pressure and subclinical cerebrovascular disease: the Northern Manhattan Study. Issue 10 (October 2015) - Gutierrez, Jose; Elkind, Mitchell S.V.; Cheung, Ken; Rundek, Tatjana; Sacco, Ralph L.; Wright, Clinton B.
Abstract : Objectives: To assess whether pulse pressure (PP) is associated, independently of mean arterial pressure (MAP), with perivascular spaces (PVS), lacunar lesions presumably ischemic (LPI), and white matter hyperintensity volume (WMHV) seen on brain MRI. Methods: Participants in the Northern Manhattan Study had their blood pressure (BP) taken during their baseline enrollment visit and again during a visit for a brain MRI a mean of 7 years later. We assessed small and large PVS, lacunar LPI, and WMHV on MRI. We examined the association of SBP, DBP, MAP, and PP at baseline with subclinical markers of cerebrovascular disease using generalized linear models and adjusting for vascular risk factors. Results: Imaging and BP data were available for 1009 participants (mean age 68 ± 8 years, 60% women, 60% Hispanic). DBP was associated with lacunar LPI and WMHV, whereas SBP was associated with small and large PVS. Using MAP and PP together disclosed that the effect size for PP was greater for large PVS, whereas the effect of MAP was greater for lacunar LPI and WMHV. The effects of DBP were flat or negative at any degree of SBP higher than 120 mmHg for small and large PVS, whereas a positive association was noted for lacunar LPI and WMHV with any DBP increase over any degree of SBP. Conclusion: We report here a segregated association between the pulsatile and steady components of the BP with subclinical markers of cerebrovascular disease. These differential associations may reflect the underlying disease of these biomarkers. Abstract : Supplemental Digital Content is available in the text